The Role And Stategy Of Kopti Handayani In Developing A Weak Economy Through Tempe Tahu Craftsmanship In Salatiga, Central Java - Samtono Samtono; Tri Maryani ; Krisnawati Setyaningrum Nugraheni (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The role of Koperasi Tempe Tahu Indonesia Kopti Handayani in helping to develop economically weak communities, which need to be empowered and developed. Kopti Handayani Salatiga became the research location with the aim of describing and explaining the role of Kopti Handayani Salatiga in helping to build the community's weak economy, and what strategies Kopti Handayani Salatiga implemented to empower and develop tahu tempe craftsmen for a better economic life. This study used descriptive qualitative method. The data was collected using documentation studies and literature deemed relevant and the results of direct in-depth interviews with related parties were then analyzed descriptively. The research results obtained are: Firstly, the role played by Kopti Handayani Salatiga, regarding his role as a facilitator, mediator and as a motivator, can run well. Second, from the results of the SWOT analysis, it is recommended that the role and strategy of Kopti Handayani be very perspective and have high hopes for development and can boost the weak economic growth of the people in Salatiga